Impact assessment and sustainable resource management - Smith, L. G. L. Graham Smith (New York, Longman Scientific & Technical., 1993)
Firmly places impact assessment in the broader context of environmental planning, developing a much-needed integrative approach. The topics covered include: decision making and dispute resolution; the role of environmental law; public policy, administration and publication participation; the nature of planning; impact assessment methodology; the application of impact assessment to frontier developments; linear facilities and waste mana
Includes bibliography references and index